Determination of paraoxonase activity and prooxidant-antioxidant balance in the brain tissue of rats following subacute administration of different K-oximes - Jaćević, Vesna; Grujić-Milanović, Jelica; Milovanović, Zoran; Milanović, Sladjan; Nežić, Lana; Amidžić, Ljiljana; Vojinović, Nataša; Marković, Bojan; Dobričić, Vladimir; Milosavljević, Petar; Nepovimova, Eugenie; Kuča, Kamil (Chemico-biological interactions, 2025)
This study aimed to determine the paraoxonase activity and prooxidant-antioxidant balance in the brain tissue of Wistar rats following subacute treatment with selected K-oximes. Each K-oxime was administered intramuscularly (0.1 LD50/kg) twice per week for four weeks, and 7 days after the last treatment, the paraoxonase activity (PON1), the prooxidant-antioxidant balance (PAB), the levels of superoxide anion radical (O2•-), the concentration of nitrite (NO2-) and the content of free protein thiol groups in the brain homogenates were evaluated. The PON1 and PAB activity were significantly reduced in almost all oxime-treated groups (p < 0.01 and p < 0.001, respectively). The concentrations of O2•- were significantly increased in the obidoxime-, K048-, K074- and K075-treated groups (p < 0.001), while the levels of NO2- was significantly decreased in asoxime-, obidoxime-, K074 and K075-treated rats (p < 0.01, p < 0.001, respectively). The content of Thiol groups was significantly elevated in all oxime-treated groups (p < 0.001). Continuing our previously published data, these results confirmed that applied K-oximes improved the oxidative status and further harmful systemic effects of rats after subacute administration.
Keywords: superoxidy; oximy; Nitrites; krysa rodu Rattus; Aryldialkylphosphatase; Superoxides; dusitany; potkani Wistar; antioxidancia; Oximes; Sulfhydryl Compounds; Rats, Wistar; mužské pohlaví; zvířata; Rats; Animals; Male; mozek; sulfhydrylové sloučeniny; Brain; Antioxidants; aryldialkylfosfatasa